TWO ASYMMETRICAL PERMIAN GRANITIC BELTS IN THE SOUTHEAST CAOB AND THEIR IMPLICATIONS - Ying Tong; Tao Wang; Lei Guo; Lei Zhang; Jianjun Zhang (Геодинамика и тектонофизика)
There has been much discussion about the evolution of the Southeastern CAOB in the past two decades [Tang, 1990; Hong et al., 1994; Xiao et al., 2003; Li, 2006; Chen et al., 2009; Jian et al., 2010]. Most people believed that the Palaeozoic Asia ocean was closed along the Solonker suture at Permian with two-direction subduction models [Xiao et al., 2003; Jian et al., 2010]. Three EW subparallel Permian granitic belts took place both side of the Solonker suture, including Erlian-Uliastai belt on north side of the Erlian-Hegengshan ophiolite, south Mongolia-Xilinhot belt the Erlian-Hegengshan ophiolite on the north and the Solonker suture on the south, and the Baotou-Chifeng belt along the north margin of North China Carton on the south of the Solonker suture. Most Permian granitoids in the ErlianUliastai belt and Mongolia-Xilinhot belt were intruded in Early-Middle Permian.